Training on Early Detection of Stroke for Health Cadres to Prevent Disability After Stroke in the Kebonsari Village Area - Septianingrum, Yurike; Sari, Ratna Yunita; Hatmanti, Nety Mawarda; Wijayanti, Lono; Firdaus, Firdaus; Yuniati, Dyah (Universitas Malahayati Lampung, 2024)
ABSTRACT Early detection of stroke is an effort to prevent more severe disability in stroke patients. Delays in bringing stroke patients to the hospital are one of the reasons why patients miss the golden period of stroke treatment. Health cadres play an important role in identifying health problems in the community, but most cadres do not understand how to carry out early stroke detection. To increase the knowledge and ability of cadres in detecting strokes so that treatment does not exceed the golden period of strokes. The method used in this community service activity is a participative educational approach, including providing health education and demonstrations regarding early stroke detection. This activity was conducted in April 2023 and was attended by 35 health cadres. Knowledge and ability to detect stroke are evaluated used knowledge questionnaire instruments and observation sheets. The results of community service show that the knowledge and ability to perform stroke detection among cadres has increased after training. Cadres' knowledge and ability to detect stroke in the health community can be improved through early stroke detection training. It is hoped that trained health cadres can provide health education to other residents to increase residents' knowledge about stroke and when is the right time to take patients to hospital. Keywords: Early Detection, Health Cadres, Non-Communicable Disease, Stroke